Uji Efektivitas Ekstrak Jahe Merah (Zingiber officinale var. rubrum) Terhadap Pertumbuhan Jamur Candida albicans Dan Sumbangsihnya Pada Materi Fungi Di SMA/MA - Erlita erlita; Jhon Riswanda; Ummi Hiras Habisukan (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2022)
Candida albicans is a pathogenic fungal species from the deuteromycota group. This fungal species is the cause of opportunistic infections called candidiasis of the skin, mucosa, and internal organs of humans. Traditionally, red ginger extract (Zingiber officinale var. rubrum) has been used for various ingredients such as increasing endurance, overcoming inflammation, coughs, wounds, and allergies due to insect bites. This study aims to test the effectiveness of red ginger extract (Zingiber officinale var. rubrum) against the fungus Candida albicans and to determine the concentration of inhibition of red ginger extract (Zingiber officinale var. rubrum) which can inhibit the growth of Candida albicans. This research method uses experimental methods and The design of this study was Completely Randomized Design with 4 treatments and 6 repetitions. The data analysis technique used ANOVA analysis of variance to examine the differences between more than two groups. The concentrations used in this study were 25%, 50%, and 100%, and the negative control used DMSO. Based on the results of the research with a test level of 1% that the red ginger extract (Zingiber officinale var. rubrum) on the growth of the fungus Candida albicans gave a very significant effect because Fcount > Ftable (78.325>3.10) against the fungus Candida albicans so Ha was accepted, H0 was rejected. The highest average inhibition zone in this study was at a concentration of 100% with a value of 13.14, the average 50% inhibition zone resulted in a value of 11.19 mm and the lowest average inhibition zone was at a concentration of 25% with a value of 9.77 mm. This shows that red ginger extract (Zingiber officinale var. rubrum) has an effect on the growth of the fungus Candida albicans. As for the results of the Duncan's Real Distance Difference Test (BJND) at the treatment concentrations P0, P1, and P3 there were real differences at distances 1, 2 and 3 which were significantly different